Who drives smart growth? The contribution of small and young firms to inventions in sustainable technologies - Birgit Aschhoff; Georg Licht; Paula Schliessler (WWWforEurope, 2013)
Europe's innovation potential is currently dominated by well-established large companies. In most member countries the bulk of R&D expenditures is spend by large companies. Following OECD data, SME's share in total R&D spending amount to 8% in Germany or Japan, around 15% in US, France, Korea or Italy, about 20% in Sweden, Finland or Switzerland, about 30% in Netherlands, Austria or Poland, and about 50% in Poland, Ireland, Slovakia or Greece. First of all, these figures point to a considerable heterogeneity with regard to the importance of SMEs in national R&D activities. However, young companies are said to be the driving force behind radical innovation which will be a source of employment and growth in future. In addition, the weakness of Europe is not only the small number of hightech startups but more specifically the number of hightech startups which accomplish continuing, rapid growth. However, there might be significant technology specific heterogeneity with regard to the contribution of SMEs and young firms to innovation. The central question of the paper is whether SMEs and young firms might be agents with a special contribution to new growth path in Europe. We took new renewable energy technologies as an example at test whether the contribution of SMEs and young firms is larger in this technology area compared to invention as measured by patenting. In order to focus on the most valuable patents we use patent applications at the European Patent Office which were also applied for patent production at the USPTO and the Japanese Patent Office (“triadic patent applications”). The analysis proceed in two steps: The paper looks first at trends in international patenting and compares triadic patent application in the field of energy with all triadic patent application by country of inventors. The idea is to highlight the role of EU and its member states in invention activity in a technology-field which is of special relevance for a new, sustainable growth path. In the second step we look at the contribution for SMEs and young firms to such a new growth path by a detail analyses of triadic patent application by German companies as the SMEs share to R&D is the smallest compared to all other EU member states as well as compared to OECD member states (except Japan). The focus on Germany is motivated for two reasons - to ease the analysis and to focus on the most extreme case of the firm-size R&D distribution which is observed in EU and OECD member states. The study employs the WIPO “Green Inventory” classification to identify energy-related patents via the international patent classification used by all patent offices to assign patents by technology and potential fields of application. This classification comprise as main technology classes alternative energy production, transportation, energy storage, waste management, agriculture/forestry, regulatory and design aspects, and nuclear power generation. The number of green inventory patents increased from 1991 to 2007 by a factor of 2.5 to 12.500 patent applications. The majority of this increase is observable in renewable energy product, storage of energy, design and management of energy systems, and waste management. Patents related to nuclear power account for 4% of green inventory patents and this share declined even more to 1% in 2007. Surprisingly, the increase of green inventory patent applications at the EPO more or less equals the increase in overall patent applications at the EPO. Hence, the share of green inventory patents in total patent application at EPO was constant and fluctuating always between 8-10% with not visible trend. Similarly, albeit the increase in the number of triadic patents is less impressive (only by a factor of 1.4) the structural features are the same. Overall, the importance of green patent activities does not greatly vary between countries or regions. In 2007, the share of green patent applications in all patent applications at the EPO lies between 7% and 12%. Interestingly, the new member states and southern Europe are at the upper end of the range (12% and 10%, respectively) - besides Japan (11%) and the US (10%). Green patents are slightly less important for Northern Europe and China (both 7%). Focusing on more valuable patent application (“triadic patent application”), green technologies become more important in Germany, Korea and China and lose importance in Southern Europe. The second step linked sustainable growth to the “entrepreneurial” economy by examining to which degree small and young firms are driving sustainable patenting. We find SMEs to be responsible for about 15% of all patent applications. This is the same for the WIPO Green Inventory classified “green” patents. Around half of patent applications of SMEs are made by young firms. About one half of all patent applications by SMEs are filed by micro firms. When narrowing down the analysis to triadic patents, we find the contribution of SMEs to decrease to about 9% of all patent applications which is probably caused by the larger costs of applying and maintaining triadic patents than EPO patents. The contribution to green patenting is even lower for triadic patents with only 6% of all green patents coming from SMEs. In the third step of the analysis, based on the link of German firm data to patent applications at the European Patent Office, we analyzed at the firm level whether small and young firms are more or less likely to file sustainable patents than other firms. The results show that large firms are significantly more likely to file both patents in general and green patents. We do find that, for micro, small and medium size firms, the negative effect on patenting compared to the reference category of a large firm is less strong for the younger firms. This effect exists both for the generation of patents in general and the generation of green patents. Therefore there does not seem to be a particular advantage for small or young firms in producing sustainable, green patents. Even more, SMEs and young firms seem to face larger obstacles to start inventing in green energy technologies than in other technology fields. In any case SMEs and young firms will probably not an important driver of new technologies like in some other fields of technology. Of course we have to admit that our same only covers international patent applications for the priority year 2007 or earlier. Hence, things might have changed in the meantime due to e.g. extended government support for innovation in green energy fields. However, this question can only be examined with future editions of the PATSTAT data which fully covers more recent years. In addition, we cannot rule out the SMEs and/or young firms are especially important for patents which are radical driver of technological change. To address this question several measurement issues need to be solved and/or existing measurement approaches need verification. However, this is beyond the limits of our study. What might be the contribution to the central questions of the wwwforEurope project? First of all, young and small firms might not able to drive the technology development towards a more sophisticated use of energy resources and renewable energies. Like in most other fields of technology the direction of technical change is determined by established large firms. Hence, under the current framework of innovation and industrial policies, the development of the “more entrepreneurial economy” will probably not form forerunners on the ways towards a new growth path. Secondly, private sector's production of invention activities became not stronger directed towards technologies which aim at production, storage, distribution, and management of new energy technologies compared to other fields of technology. Given the societal need for new energy technologies the paper speaks in favor of government regulation, invention and incentives to stimulate research, development, and implementation new energy technologies. However, we do not find arguments that such stimuli should favor SMEs or young firms.
Keywords: O31; M13; C81; 330; Green patents; sustainable patenting; SMEs; young firms